Fifth Five Year Plan Proposal Vol. 4, Government of Tripura Planning & Coordination Department - Planning Commission (Planning Commission, 1973)
The proportion of Scheduled Tribe population to total population of Tripura has been going down as will be evident from the figure above. This is because of heavy influx of refugees in Tripura since partition. It has also given rise to increasing pressure on land and most of the Tribals, by virtue of their peculiar nature have tended to go deeper and deeper into the hills. Consequently, most of the Tribals depend on shifting cultivation for which also there is not enough land. Their inability to take to settled cultivation in the comparatively lower reaches coupled with dependence on shifting cultivation has stalled the development of tribal people to a great extent. Another factor which is responsible for their slow progress is the scattered nature of their hamlets which remain untouched from the normal development activities of the various Departments. It is, therefore, very important that- all development Departments should make special efforts to extend benefits to this section of population, while the Tribal Welfare Department supplements their efforts.
Fifth Five Year Plan Proposal
Government of Tripura